Does the mandatory disclosure of suppliers' tax uncertainties affect supply chain relations? - Tao, Xuedan; Wang, Huabing Barbara; Xin, Qian; Xu, You (Journal of Corporate Finance, 2024)
We investigate whether and how the public revelation of tax uncertainty affects supply chain relations by utilizing an exogenous shock to tax reporting under FIN 48, which mandates the disclosure of uncertain tax benefits (UTBs). Using a difference-in-differences research design, we find that firms disclosing UTBs experience a significant decrease in sales to major customers after FIN 48 relative to firms without tax uncertainty. Further mechanism analyses suggest a risk perception channel that the disclosure heightens customers' risk perception of the suppliers: the adverse effect is more pronounced for suppliers with higher tax uncertainty or ex ante corporate risk. However, we do not find evidence for a tax morale channel that customers are concerned about sourcing from a “bad corporate citizen.” In cross-sectional analyses, we find a stronger adverse effect when customers and suppliers are less likely to engage in private information sharing or tax coordination, when suppliers disclose higher-quality UTBs, or when customers have lower tax risk tolerance or switching costs. Overall, our findings document an externality of tax disclosure from the perspectives of supply chain partners, suggesting that the disclosure of tax uncertainty provides valuable information to corporate customers and affects a firm's trade relations.